Obstetric anal sphincter injury and incontinence 15–23 years after vaginal delivery. (7th April 2016) - Halle, Tuva K.; Salvesen, Kjell Å.; Volløyhaug, Ingrid
Abstract: Introduction: The primary aim was to study prevalence of obstetric anal sphincter injuries (OASIS) after normal vaginal deliveries (NVD) and operative vaginal deliveries (OVD) with a subgroup analysis of forceps (FD) vs. vacuum deliveries (VD). The secondary aim was to study the association between OASIS and anal incontinence 15–23 years later. Material and methods: This was a cross‐sectional study including 8137 primiparous women in Trondheim, Norway, from 1990 to 1997. The outcome measure was the adjusted odds ratio (aOR) for OASIS between delivery groups. A total of 1122 women responded to a postal questionnaire containing the Colorectal‐Anal Distress Inventory (CRADI) in 2013. The aOR for anal incontinence and the difference in CRADI score between women with and without OASIS were calculated. Results: OASIS prevalence was 2% for NVD and 10% for OVD (10% FD, 9% VD). aOR for OASIS was 5.01 (95%CI 3.85–6.51) comparing OVD with NVD. There was no difference between FD and VD (aOR 1.15, 95% CI 0.79–1.67). FD was associated with higher risk of fourth degree perineal tear than VD (aOR 5.08, 95% CI 1.47–17.49). OASIS was associated with increased risk of leakage of well‐formed (aOR 8.61, 95% CI 3.08–24.12) and loose stool (aOR 2.75, 95% CI 1.43–5.27) and higher CRADI score (Mann–Whitney U ‐test, p = 0.01). Conclusions: OVD was associated with increased risk of OASIS. FD was associated with higher risk of fourth degree perineal tear compared with VD. OASIS was associated with increased risk of anal incontinence and higher CRADI score 15–23 years later.